Percepção ambiental e turismo sustentável: análise dos impactos da atividade turística em zonas costeiras da grande João Pessoa PB - Silva, Michel Robinson de Oliveira (2014)
Despite the positive character promoted by the tourism industry, developing regions and generating employment and income, if not planned, it also brings negative effects, on social aspects, and, especially, in environmental. When practiced in fragile ecosystems such as coastal areas, the degradation potential of tourism can be even greater if there is no proper management and administration of the activity. Thus, the trend of sustainability emerges as an essential alternative in activity practice, because it allows the use of natural resources for recreational purposes consciously, ensuring its perpetuation for many years. Studies of perception and the use of tools such as environmental education are important to evaluate the profile of those who deal with tourism, enabling know their behaviors and values on environmental issues and also trying to sensitize them about the importance of conservation areas used. In this context, the present study aimed to analyze the environmental perception of four groups connected to tourism (tourists, residents, businesses/professionals and agents) practiced in three coastal areas of great João Pessoa: Praia do Jacaré, Areia Vermelha and Picãozinho. In addition to evaluating some environmental practices of these ones, also identified the main environmental impacts that occur in these spaces as a result of tourism, according to the judgment and opinion of the interviewees themselves. The objective was to identify measures and suggestions, based on environmental education and awareness tools, that might help in the planning and sustainable management of tourism, conserving natural resources of these explored areas. The survey was conducted between January and May 2013, reaching a total of 491 people. Overall, the most frequently reported impacts in the three zones were changing the natural landscape, the wear of coral reefs, noise pollution and water/sea pollution by garbage. Regarding environmental practices, all groups have indicated that they have the habit of saving resources such as water and electricity in their homes and also when traveling. In separating garbage (at home and when traveling), most groups indicated that they do. Others said do not justifying that they don t know how. Considering the three areas, all groups showed an interest in taking some action that seeks to improve the environment and tourism in these places. In the analysis of environmental perception, people who work in the agencies and who live in the coastal region near Picãozinho were the only groups that have demonstrated an ecocentric profile. All the other groups (tourists, residents of Praia do Jacaré and around Areia Vermelha and all companies/professionals) had anthropocentric and indifferent profiles according to the environmental issues.